MODERATING EFFECT OF FIRM ENVIRONMENTAL SENSITIVITY ON THE RELATIONSHIP BETWEEN SUSTAINABILITY REPORTING DIMENSIONS AND FINANCIAL PERFORMANCE OF AN EMERGING MARKET ECONOMY - Adedeji Daniel GBADEBO (Gusau Journal of Accounting and Finance)
This study examines the moderating role of firm environmental sensitivity on the relationship between sustainability reporting dimensions, environmental, social, and governance disclosures, and the financial performance of nine listed oil and gas firms in Nigeria from 2019 to 2023. Employing panel data analysis and interaction models, the results reveal that environmental and social reporting have a positive influence on financial performance, while governance reporting shows an insignificant effect. Firm environmental sensitivity significantly moderates the impact of environmental reporting on financial outcomes, underscoring the importance of contextual industry factors in enhancing the value of sustainability disclosures. The findings contribute to the literature by integrating firm-specific environmental sensitivity into the analysis of sustainability reporting effectiveness, providing valuable insights for regulators, investors, and corporate managers aiming to optimize sustainability practices within environmentally sensitive sectors.